Case report: Highly differentiated endometrial adenocarcinoma that collided with uterine cervical carcinosarcoma - Fan, Xue; Hu, Haoyue; Liu, Yang; Tan, Songtao; Xie, Meng; Zhang, Fang (Frontiers in Medicine, 2023)
Rational: Uterine collision tumor is a rare pathological type composed of two or more malignant tumors with rare related reports and its diagnosis is mainly depend on pathological examination. The causes of uterine collision tumors are unclear. At present, there is no standard treatment guideline for uterine collision tumor and comprehensive treatment composed of chemotherapy, radiotherapy and surgery.